Israel dalam Teks-Teks Agama Islam - Otong Sulaeman (Indonesia Center for Middle East Studies, 2018)
There are two perspectives which link Islam with the Israeli-Palestinian conflict. The first perspective believes that the conflict in Palestine is an inter-religious conflict, namely Islam versus Judaism. The second perspective sees that the conflict in the region is not an interfaith battle, but rather a battle between two entities: the invaders and the colonized. However, this second perspective still uses religion as a foundation to defend the Palestinian people because the principle of opposing the tyrant does exist in the teachings of Islam. In this article, the author will present the Qur'anic texts about Israel. The author found, there are two types of the verses of the Qur'an that describe the Jews: first, as a group with various bad qualities; second, verses that describe the Jews positively.